In vitro comparisons of casting retention on implant abutments among commercially available and experimental castor oil-containing dental luting agents - Pinelli, Lígia A.P. [UNESP]; Fais, Laiza M.G. [UNESP]; Ricci, Weber Adad [UNESP]; Reis, José M.S.N. [UNESP] (Elsevier, 2013)
Statement of problem Although cement-retained implant prostheses are widely used, the quantification of optimal retention remains controversial, and new dental luting agents should be evaluated. Purpose The purpose of this study was to compare, in vitro, the casting retention on implant abutments after cementation with 3 commercially available luting agents and an experimental luting agent (castor oil polyurethane, COP) with variable weight percentages (wt%) of calcium carbonate (CaCO3). Material and methods Seventy-two palladium-silver cast copings were fabricated and divided into 6 groups: Temp Bond interim cement (TB); zinc phosphate cement (ZP); Rely X ARC resin cement (RX); pure COP (COP); COP + 10% wt% CaCO3 filler (COP 10); and COP + 50% wt% CaCO3 filler (COP 50). After cementation, the specimens were stored in distilled water at 37°C for 24 hours and subjected to removal force tests in a universal testing machine (5 kN; 0.5 mm/min). Statistical analyses were performed with the Kruskal-Wallis and Student-Newman-Keuls tests (α=.05). Results The median values of casting retention (N) were as follows: TB=57.20 ±10.4; ZP=343.56 ±50.3; RX=40.07 ±9.7; COP=258.98 ±41.4; COP 10=466.57 ±79.3; and COP 50=209.63 ±31.4. The Kruskal-Wallis test showed significant differences among the groups (P<.01). TB and RX had the lowest mean retention values; COP, COP 10, and COP 50 were equal to ZP, and COP 10 had the highest retention. Conclusions The casting retention on implant-abutments provided by COP was similar to that of copings cemented with zinc phosphate and may be influenced by the addition of calcium carbonate. © 2013 The Editorial Council of the Journal of Prosthetic Dentistry.